"The same contract that is suitable for your Excellency": Immigration and emulation in the adoption of sharecropping-cum-debt arrangements in Brazil (1835-80) - Bruno Gabriel Witzel de Souza (The Economic History Review, 2023)
This paper studies the history of contractual choice in coffee plantations of S\~ao Paulo, Brazil. It focuses on the consolidation of non-captive labour markets in the early phases of the transition from slavery in the country, particularly in the 1840s–50s. Vis-à-vis the alternatives of fixed rents and fixed payments per time worked or piece rates, the paper examines the rationale for the adoption of sharecropping arrangements with European bonded labourers. New archival evidence suggests that sharecropping had no obvious productivity advantage over alternative labour–rental arrangements in this period, and that the adoption of sharecropping arrangements resulted from the positional advantage of its first proposers, who influenced later choices of contractual design. A credit-labour tie-up long outlived the original sharecropping arrangements, in turn allowing for the immigration of poor and credit-constrained Europeans, paving the way to insert Brazil into the circuits of mass migration without promoting institutional reforms to attract non-bonded immigrants.
Keywords: 330; Brazil; coffee; fixed rents; immigration; piece rates; plantations; S\~ao Paulo; sharecropping; slavery; wage system